Improving learners’ critical thinking and learning engagement through Socratic questioning in Nominal Group Technique - Alies Poetri Lintangsari; Ive Emaliana; Irene Nany Kusumawardani (Studies in English Language and Education, 2022)
Critical thinking is assumed as one of the essential skills in today’s era. One of the ways to foster students’ critical thinking is through discussion that provokes their curiosity. Unfortunately, in the online setting, some studies reported that students face challenges in online discussion.  Therefore, teachers should find a way to optimize students’ engagement in online discussions. The Nominal Group Technique (NGT), which this paper argues for proposing a potential way in improving students’ participation and their critical thinking in an online discussion, is less used as a teaching strategy in educational practices. With the integration of Socratic Questioning, this research implemented a pre-experimental method with a one-shot design aimed at investigating the effectiveness of the NGT implementation in Critical Reading Classes conducted online combining both synchronous and asynchronous settings. Pre- and post-tests were implemented in two classes involving 52 students in six meetings. The descriptive statistics and t-test analysis had been implemented to find out the differences in students’ critical thinking skills before and after the NGT implementation. The result showed that there was a significant improvement in students’ critical thinking skills at p0.001, which confirmed that NGT with the integration of Socratic Questioning had a significant effect on the improvement of students’ critical thinking skills in an online context.